Historia clínica, exámen físico y estrategias adicionales para desórdenes temporomandibulares y dolor orofacial II - Acosta, Rodolfo (Revista Estomatología, 2002)
This article presents a physical exam protocol for the clinical evaluation of temporomandibular disorders and orofacial pain patients. The process of evaluation, after the clinical history, is finished by a physical exam and when necessary, additional strategies are used. The purpose of this article is to present the physical exam and the use of the additional strategies which include provocation tests, diagnostic aids and additional consultation. This will allow the clinician to make an adequate connection with the data collected in the clinical history that will also help in the establishment of the differential diagnosis as well as presenting the correct strategies of management.